Uso de aguapé (Eichhornia crassipes) em sistema de tratamento de efluente de matadouro e frigorífico e avaliação de sua compostagem - Mees, Juliana Bortoli Rodrigues (2006)
The objective of the recent research was to evaluate the water hyacinth performance (E. crassipes), applied in situ in a slaughter house treatment system, located in the west of the Paraná state, observing the nutrients removal (nitrogen composts and total phosphorus), organic matter (COD and BOD), turbidity and suspended solids, obtaining as well data from the production, management and composting practices of the biomass generated in the system. The plants were introduced into the forth tank of the industry stabilization lagoons system, covering 35m2 of the total area delimitated for the experiment: 870m2. During a period of 11 months (47 weeks) of water hyacinth development, physic and chemical parameters were monitored monthly and meteorological parameters were monitored daily or weekly. In order to search information about the degradation of the water hyacinths removed from the treatment, another experiment was conduced in plant pilot. Eight composting piles were built measuring approximately 0.60m3, with four distinct treatments that were done twice. The treatments were T1 - Water hyacinth (E. crassipes), T2 - Water hyacinth and swine excrement (7:1), T3 - Water hyacinth, swine excrement and earth (7:1:0,67), T4 - Water hyacinth, swine excrement and cellulosic gut (7:1:0,67), for a period of 90 days. The temperature was monitored daily, and humidity, cinder, nitrogen and total organic carbon were monitored monthly. The result obtained, during 11 months, were promising and the efficient averages of 26.3% of COD and 32.5% of BOD removal were observed, with a maximum removal of 77.2% of COD and 77.87% of BOD. About the nutrient removal, a 21.2% average of nitrogen removal was observed, with a maximum removal of 87.9%, an 11.0% average for ammoniac nitrogen, with maximum of 47.5%, and an 11.1% average and maximum of 38.9% for total phosphorus, during an average of 5 days of retention. An increase in the water turbidity was noticed during the months of high pluviometric precipitation; however, the efficiency of the process was positive during all the monitoring period, with a maximum removal of 58.1%. Considering the C/N relation as a compost maturity indicator, the T4 treatment (water hyacinth, swine excrement and cellulosic gut) had the shorter period of stabilization: 60 days.